Stress‐Related Changes in Toddlers and Their Mothers Following the Attack of September 11. (28th October 2013) - Conway, Anne; McDonough, Susan C.; MacKenzie, Michael J.; Follett, Chantal; Sameroff, Arnold
Abstract : Unlike other forms of disaster, terrorism is not confined to a particular place or time, and recent evidence indicates that the 9/11 terrorist attack was a significant macrolevel stressor affecting the health and mental health of United States citizens. No studies, however, have reported symptoms in toddlers and their mothers both before and after the attacks. To address this gap, we examined the effects of the 9/11 terrorist attacks on mothers and their 33‐month‐old toddlers. The attacks occurred during data collection at 33 months of a longitudinal study. Thirty‐three‐month‐old toddlers and mothers who were assessed after the attacks were compared with those assessed before the attacks. When changes were examined from a previous wave of data collected at 15 months, those in the after‐attack group showed poorer health, lower child acceptance, and marginally more anxiety, and their toddlers cried more and slept less, whereas the before‐attack group showed no changes. Our findings contribute to research documenting widespread effects of the 9/11 terrorist attack on stress‐related symptoms and suggest that greater attention must be placed on the needs of our youngest citizens and their caregivers.